PENGEMBANGAN MEDIA PEMBELAJARAN PUZZLE PADA MATERI BILANGAN BULAT KELAS IV SD NEGERI 37 PEKANBARU - Novita Febrina; Eddy Noviana; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: the use of instructional media will greatly assist the effectiveness of the learning process and the delivery of learning materials. The purpose of research is to develop and determine feasibility learning media puzzle on material integers fourth grade of elementary school. This research was conducted at the university FKIP Elementary School Teacher Elementary School and the University of Riau 37 Pekanbaru. type of research is the development by Sugiyono, but is limited to the testing stage product limited scale. The instrument used to collecting the data is validation feasibility puzzle pieces as a learning medium that is filled by three validator. Furthermore, the trial is limited to 31 elementary students in the form of questions and questionnaires reson students who performed at the SD Negeri 37 Pekanbaru. The data is then analyzed using descriptive analysis. The results of the validation of the feasibility of the development puzzle that can be seen in terms of media and materials. Overall results validate the feasibility Puzzle a percentage of 93.33% categorized as very feasible, does not need to be revised. The trial results are limited effectiveness of media seen an increase in the gain by 0.84 high category and student response for good learning media puzzle with a percentage of 86.29%.Keywords: Puzzle, Media Learning, development Research, integers